2015
DOI: 10.1016/j.cjca.2015.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Adaptation and Failure in Pulmonary Arterial Hypertension

Abstract: Pulmonary arterial hypertension (PAH) is an obstructive pulmonary vasculopathy, characterized by excess proliferation, apoptosis-resistance, inflammation, fibrosis and vasoconstriction. While PAH therapies target some of these vascular abnormalities (primarily vasoconstriction) most do not directly benefit the right ventricle (RV). This is suboptimal since a patient’s functional state and prognosis are largely determined by the success of the adaptation of the RV to the increased afterload. The RV initially hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
102
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(119 citation statements)
references
References 124 publications
3
102
0
3
Order By: Relevance
“…J, Exercise tolerance decreased in DRV rats (n=6) compared with controls (n=11) and significantly improved in rats treated with mimic-126 (n=4) compared with DRV+vehicle (n=5 systolic function in PAH, RV adaptation to this increased afterload depends not only on the severity of pulmonary vascular disease but also on changes in myocardial metabolism, rate of myocardial hypertrophy and fibrosis, and adaptation of the capillary network. 36 This complex interplay likely explains the significant variability in RV adaptation to PAH between patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…J, Exercise tolerance decreased in DRV rats (n=6) compared with controls (n=11) and significantly improved in rats treated with mimic-126 (n=4) compared with DRV+vehicle (n=5 systolic function in PAH, RV adaptation to this increased afterload depends not only on the severity of pulmonary vascular disease but also on changes in myocardial metabolism, rate of myocardial hypertrophy and fibrosis, and adaptation of the capillary network. 36 This complex interplay likely explains the significant variability in RV adaptation to PAH between patients.…”
Section: Discussionmentioning
confidence: 99%
“…J, Exercise tolerance decreased in DRV rats (n=6) compared with controls (n=11) and significantly improved in rats treated with mimic-126 (n=4) compared with DRV+vehicle (n=5 systolic function in PAH, RV adaptation to this increased afterload depends not only on the severity of pulmonary vascular disease but also on changes in myocardial metabolism, rate of myocardial hypertrophy and fibrosis, and adaptation of the capillary network. 36 This complex interplay likely explains the significant variability in RV adaptation to PAH between patients.In keeping with several previous studies in RV failure, 8,37 our study showed that, as in experimental PAH, 8,9 human RV failure is associated with decreased capillary density ( Figure 1A). Recently, Sutendra et al 8 proposed that, in the monocrotaline-induced PAH rat model, CRVH is characterized by a metabolic switch from oxidative phosphorylation to a glycolytic state, allowing the activation of HIF-1, increasing VEGF expression, and preserving angiogenesis.…”
mentioning
confidence: 99%
“…In PAH, obstructive remodeling of the pulmonary vasculature and reduced PA compliance increase pulmonary arterial pressures and right ventricular (RV) workload 4, 5. As PAH progresses, RV function declines, and many patients succumb from RV failure 6, 7. Although RV dysfunction is repeatedly identified as the major risk factor for mortality in PAH,8, 9, 10 the 4 classes of approved pulmonary hypertension medications primarily target the pulmonary vasculature, with little evidence of direct benefit to the RV.…”
Section: Introductionmentioning
confidence: 99%
“…1) Progressive increase in pulmonary artery pressure eventually leads to right ventricular hypertrophy (RVH), RV failure (RVF) and ultimately death.…”
mentioning
confidence: 99%